1972
DOI: 10.3382/ps.0511122
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Photoperiod During Incubation on Embryonic and Post-Embryonic Development of Broilers

Abstract: Four experiments were conducted to determine the effect of light during incubation on embryonic and post-embryonic development of broiler chickens. The eggs were randomly assigned to one of three lighting regimes during the incubation period: (a) a diurnal light cycle consisting of a 12-hour light period followed by a 12-hour dark period (12L-12D), (b) 24 hours of light (24L-OD), and (c) 24 hours of darkness (0L-24D) per day.The development of the embryos was accelerated by increasing the length of exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
2

Year Published

1975
1975
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 2 publications
3
19
2
Order By: Relevance
“…However, when comparing light and dark incubated eggs, regardless of yolk pigmentation, a 12 to 15 hr difference in mean hatch time was observed. Differences in hatch times of light versus dark incubated eggs were in agreement with a number of workers who have reported differences in hatch time due to lighted incubation of from 5 hr to 2 days (Walter and Voitle, 1972;Siegel et al, 1969;Coleman and McDaniel, 1975). However, the differences in hatching time reported in this study were not of the magnitude of Coleman and McDaniel (1975), who reported that White Leghorn eggs exposed to lighted incubation conditions comparable to those of this study hatched on the 18th and 19th day of incubation.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…However, when comparing light and dark incubated eggs, regardless of yolk pigmentation, a 12 to 15 hr difference in mean hatch time was observed. Differences in hatch times of light versus dark incubated eggs were in agreement with a number of workers who have reported differences in hatch time due to lighted incubation of from 5 hr to 2 days (Walter and Voitle, 1972;Siegel et al, 1969;Coleman and McDaniel, 1975). However, the differences in hatching time reported in this study were not of the magnitude of Coleman and McDaniel (1975), who reported that White Leghorn eggs exposed to lighted incubation conditions comparable to those of this study hatched on the 18th and 19th day of incubation.…”
Section: Resultssupporting
confidence: 90%
“…Numerous authors, using various lighting regimens, have demonstrated that light accelerates embryonic development (Schutze et al, 1962;Lauber and Schutze, 1964;Siegel et al, 1969;Isakson et al, 1970;Walter and Voitle, 1972;Garwood et al, 1973;Coleman and Mc-Daniel, 1975).…”
Section: Introductionmentioning
confidence: 96%
“…Early studies indicated that white-light illumination accelerates embryonic development of several avian species (6,7,38,46). Eggs incubated under white light hatched ϳ1 day earlier than those incubated in the dark (7,38,45). Continuous green-light illumination reduced embryo mortality in chicks (36).…”
mentioning
confidence: 98%
“…It is well known that temperature and humidity affect both hatchability and hatching time (Landauer, 1948). Additionally, photoacceleration of embryonic development occurs in the presence of light during incubation (Walter and Voitle, 1972). The influence of EMG fields on hatchability and hatching time of chicken eggs had not been previously considered.…”
Section: Resultsmentioning
confidence: 99%